2022
DOI: 10.1177/00208728221091125
|View full text |Cite
|
Sign up to set email alerts
|

Poverty in Arab-Palestinian society in Israel: Social work perspectives before and during COVID-19

Abstract: Arab-Palestinian families have one of the highest poverty rates in Israel. However, there is a lack of knowledge regarding this population from a social work perspective. This article presents an analysis of 64 supervision sessions held with Arab-Palestinian social workers with the aim of identifying context-specific knowledge on the barriers service users face in their daily lives. Our findings point to three types of barriers: economic, sociopolitical, and cultural/political. The article relates to the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…All the studies that examined social workers' attitudes found that they developed a degree of critical analysis during the PAP training and ongoing supervision, e.g., [31,33]. A quantitative study that investigated the attitudes of 127 social workers before and after PAP training courses found significantly higher scores in the perception of poverty as structural and in acknowledging the relational and symbolic aspects of living in poverty at T2 [31].…”
Section: Social Workers' Attitudes Toward Poverty and People In Povertymentioning
confidence: 99%
“…All the studies that examined social workers' attitudes found that they developed a degree of critical analysis during the PAP training and ongoing supervision, e.g., [31,33]. A quantitative study that investigated the attitudes of 127 social workers before and after PAP training courses found significantly higher scores in the perception of poverty as structural and in acknowledging the relational and symbolic aspects of living in poverty at T2 [31].…”
Section: Social Workers' Attitudes Toward Poverty and People In Povertymentioning
confidence: 99%